Antibacterial activity, quality and stability study of creams with new potential silver(I) complexes and in vivo case report - Sovová Simona; Megyesi Štefánia Laca; Mudroňová Dagmar; Mudroň Pavol; Harvanová Jarmila; Rendošová Michaela; Goga Michal; Tkáčiková Ľudmila; Vargová Zuzana (Acta Pharmaceutica)
The aim of this study was to evaluate the antibacterial activity, quality and stability of creams (at 1 % concentration) prepared with synthesized silver(I) complexes: [Ag(Nam)2]NO3·H2O ( AgNam), [Ag2(HGly)2]n(NO3)2n (AgGly) (Nam – nicotin-amide, Gly – glycine) and silver(I) sulfadiazine (AgSD), which is commercially available. Antibacterial activity was evaluated by agar well diffusion method and in in vivo case. The pure silver(I) complexes as well as all three tested creams loaded with AgGly, AgSD and AgNam showed antibacterial potential. Moreover, the creams loaded with AgGly and AgNam showed higher antibacterial effects against S. aureus and B. subtilis than the cream loaded with AgSD. In terms of appearance, all cream samples were opaque and odourless, and no phase separation was observed. Creams were soluble in water (o/w emulsions) and they had a pseudoplastic behaviour. The pH of the creams was in the range of 4.87–5.75. No visible changes were observed in the case of commercially used AgSD cream during one month testing period at conditions –16 ± 1 °C; 6 ± 1 °C and 56 % relative humidity; 20 ± 1 °C and 58 % relative humidity and 40 ± 1 °C and 75 % relative humidity. However, creams containing AgGly and AgNam changed their colour depending on the tested conditions.